Mucormycosis in Hematopoietic Cell Transplant Recipients and in Patients With Hematological Malignancies in the Era of New Antifungal Agents. (30th December 2020) - Miller, Matthew A; Molina, Kyle C; Gutman, Jonathan A; Scherger, Sias; Lum, Jessica M; Mossad, Sherif B; Burgess, Mary; Cheng, Matthew P; Chuang, Sally T; Jacobs, Samantha E; Melendez, Dante P; Shah, Dimpy P; et al.
Abstract: Background: The survival benefit of combination antifungal therapy for invasive mucormycosis (IM) in patients with hematologic malignancy (HM) and hematopoietic cell transplant (HCT) is not well defined. Methods: This multicenter, retrospective study included HM and HCT recipients with proven or probable IM between January 1, 2007 and December 31, 2017 from 10 transplant centers across North America. Results: Sixty-four patients with proven (n = 47) or probable (n = 17) IM defined by 2008 European Organization for Research and Treatment of Cancer/Mycoses Study Group (EORTC/MSG) consensus definitions were included. Thirty-nine (61%) were HCT recipients (95% allogeneic). Sites of infection included rhino-orbital-cerebral (33), pulmonary (30%), disseminated (19%), gastrointestinal (3%), and cutaneous (3%). Surgical debridement was performed in 66%. Initial antifungal treatment consisted of the following: lipid formulation of amphotericin B (AmB) alone (44%), AmB + posaconazole (25%), AmB + echinocandin (13%), AmB + isavuconazole (8%), posaconazole alone (5%), and isavuconazole alone (3%). All-cause mortality at 30 days and 1 year were 38% and 66%, respectively. Initial treatment with AmB plus posaconazole or isavuconazole (n = 28) was associated with a trend toward lower treatment failure compared with AmB (n = 21) (42% vs 64%, P  = .136). Conclusions: Long-term survival with IM among HM and HCT populations remains poor. However, initial use of AmB + azole in conjunction with surgery may result in less treatment failure. More evidence from prospective controlled studies is needed to confirm this observation. Abstract : Frequent combination anti-fungal therapy has not improved long-term survival in HM and HCT populations with IM. Larger, prospective studies are needed to study the incidence of IM and clinical outcomes of these ever increasing immune compromised hosts.